Pengujian Faktor-Faktor Auditor Switching Dengan Analisis Regresi Logistik Pada Perusahaan Sektor Manufaktur Di BEI - Tri Sartika Pratiwi; Padriyansyah Padriyansyah (UNIVED Press, 2023)
The purpose of this study is to know and analyze, Audit Opinion, Management Change, KAP Size, and Financial Distress have a simultaneous and partial effect on Auditor Switching. The population is manufacturing companies in the consumer goods sector that are listed on the Indonesia Stock Exchange for the 2018-2020 period. A sample of 44 companies from the consumer goods sub-sector based on the criteria that have been considered. The data analysis technique used is logistic regression. Which has four testers including: Assessing the Overall Model (Overall Model Fit), Testing the Feasibility of the Regression Model (Goodness of Fit Test), Determinant Coefficient (Nagelkerke's R Square) and Classification Matrix. The results obtained simultaneously Audit Opinion, Management Change, KAP Size, and Financial Distress have an effect on Auditor Switching. Meanwhile, partially Financial Distress has an effect but Audit Opinion, Management Change, KAP Size, has no effect on Auditor Switching.